EXACERBATION OF MULTIPLE SCLEROSIS: A CLINICAL PARACLINICAL PARADOX - Zheshko, O. M.; Shulga, O. D.; Dubinets, M. I.; Yurko, O. A.; Lopachak, O. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The purpose of our work was to find out the factors that determine the treatment tactics in the presence of signs of clinical and / or radiological exacerbation in patients with remitting multiple sclerosis. 104 patients were examined, 36.25 ± 9.81 years old. It has been established that in patients with shorter duration of the disease, the incidence of clinical (p <0.001) and radiological exacerbations (p <0.001) is higher. In patients who do not receive immunomodulatory therapy (p <0.05), there are signs of both clinical and radiological exacerbation. Patients with clinical exacerbations, regardless of the presence of active foci, receive treatment with methylprednisolone in almost 95% of cases. At the same time, in the case of radiological exacerbation, treatment with methylprednisolone is prescribed in only one third of the cases.